Pharmacological Activity of Plant Extracts in Self-Nanoemulsifying Drug Delivery System Dosage Form: Narrative Review - Julio, Ivan; Zubair, Muhammad Sulaiman; Syukri, Yandi (JSFK (Jurnal Sains Farmasi & Klinis), 2024)
The utilization of medicinal plants as therapeutic agents has obstacles to achieving the target action due to their low solubility. Self-Nanoemulsifying Drug Delivery System (SNEDDS) is a method developed to increase the solubility of poorly water-soluble substances, such as medicinal plant extracts. This review aims to present a narrative overview of the potential utilization of SNEDDS in enhancing the pharmacological activity of plant extracts. Article searches were conducted on several websites, such as Google Scholar, PubMed, and ScienceDirect. Literature studies showed that the use of SNEDDS formulations in several medicinal plants such as dayak onion, soursop leaf, papaya leaf, bay leaf, kale, sidaguri, black cumin, mangosteen peel, harendong, pineapple peel, and cocoa is more effective than the administration of extracts alone because it can increase the solubility and bioavailability of a compound. Pharmacologically, SNEDDS shows its success in enhancing antioxidant, anti-inflammatory, analgesic, antidiabetic, antihyperglycemic, antimalarial, immunostimulant, antimicrobial, anticancer, wound healing, and hepatoprotective activities in various plant extracts. The utilization of SNEDDS formulations in plant-based drugs has a positive impact on the advancement of drug therapy, especially for compounds that have low solubility.